Geography Education and Research in Nepal: Challenges, Status and Options - Pokhrel, Kabi Prasad (The Third Pole: Journal of Geography Education, 2014)
This paper discusses the development trends of Nepalese Geography and presents the status of geography teaching and research activities at university level. Facts and figures, used for discussion were assembled from the review of available geographic literature. Findings of the paper clearly indicate that there is an urgent need to redefine its directive principles in its research goals, teaching styles and social relevance. The author opines that Nepalese Geographers have to disseminate and recreate the existing knowledge of geographical science and adopt micro approach for the application of our integrated knowledge to the promotion of human welfare. DOI: http://dx.doi.org/10.3126/ttp.v13i0.11545 The Third Pole Vol. 13, 2013 page : 39-45